Kemanusiaan dalam Perspektif Kebudayaan Karo (Ketidakadilan Gender terhadap Perempuan Karo di Desa Pasar VIII N.Trasi) - Esra Natasya Br Sitepu; Yakobus Ndona (Jurnal Bintang Pendidikan Indonesia, 2024)
This research is entitled "HUMANITY IN A KARO CULTURAL PERSPECTIVE (Gender Injustice towards Karo Women in Pasar VIII N.Trasi Village)". The aim of this research is to examine what humanity really is from a Karo cultural perspective, especially in the context of gender injustice towards women in the Village. Pasar VIII N. Trasi, revealed the gap between the human values upheld in Karo culture and the social realities faced by Karo women. The method in this research is qualitative descriptive. Data collection techniques in this research include: Observation, interviews, documentation. Gender is a cultural concept that attempts to make distinctions in terms of roles, behavior, mentality and characteristics between men and women that develop in society.